2011
DOI: 10.2465/jmps.110621b
|View full text |Cite
|
Sign up to set email alerts
|

Crustal diopsidites from the northern Oman ophiolite: Evidence for hydrothermal circulation through suboceanic Moho

Abstract: This paper details a new discovery of anorthite -bearing diopsidites (= anorthite diopsidites) from the lowermost crust along Wadi Fizh in the northern Oman ophiolite. The anorthite diopsidites occur as networks within layered gabbros 50 m above the gabbro/peridotite boundary, and are mainly composed of high -Mg diopsidic clinopyroxenes and anorthites with various amounts of uvarovite. They are intermediate in mineral chemical characteristics between the crustal gabbros and the diopsidites, and interpreted as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 24 publications
1
46
0
Order By: Relevance
“…Instead, their major element compositions largely overlap those hydrothermal diopsides from the northern Oman ophiolite ( Fig. 5B; Akizawa et al, 2011;Python et al, 2007aPython et al, , 2007b, possibly suggesting they were produced by Ca-rich fluids at high temperature conditions (over 900°C; Python et al, 2007a).…”
Section: Formation Of Dispersed Clinopyroxenes By Cao-rich Fluidsmentioning
confidence: 93%
See 3 more Smart Citations
“…Instead, their major element compositions largely overlap those hydrothermal diopsides from the northern Oman ophiolite ( Fig. 5B; Akizawa et al, 2011;Python et al, 2007aPython et al, , 2007b, possibly suggesting they were produced by Ca-rich fluids at high temperature conditions (over 900°C; Python et al, 2007a).…”
Section: Formation Of Dispersed Clinopyroxenes By Cao-rich Fluidsmentioning
confidence: 93%
“…6C). However, the diopsides in the diospidites from the mantle part of Oman ophiolite display remarkable positive anomalies of Sr (average δ Sr 4.66) and Eu (average δ Eu 5.22) (Akizawa et al, 2011;Python et al, 2007b), which are not found for the dispersed clinopyroxenes. Compared with clinopyroxenes from different backgrounds, the clinopyroxenes in this study is more similar to those from the subduction zones or subcontinental lithospheric mantle, which are commonly featured by the enrichment of LILE and depletion of HFSE (Bizimis et al, 2000;Bodinier and Godard, 2007;Xu et al, 2000).…”
Section: Formation Of Dispersed Clinopyroxenes By Cao-rich Fluidsmentioning
confidence: 93%
See 2 more Smart Citations
“…This feature is taken to indicate that the vein clinopyroxenites are products of residual melt after the crystallization of abyssal peridotites. The genesis of rodingites as well as the related diopsidites is explained by extreme Ca-metasomatism of gabbroic massifs and dykes in contact with ultramafic oceanic lithospheric mantle Bach and Klein, 2009;Akizawa et al, 2011). Kelemen et al, 1995;Suhr et al, 2003), where the pyroxenes reflect the composition of percolating melts.…”
Section: Introductionmentioning
confidence: 99%